Biochemical and oxidative profile of horse used for a simulated barrel racing - Rodrigues, Isabella Manes Soutto Mayor da Motta; Spindola, Bruno Ferreira; Botteon, Paulo de Tarso Landgraf (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Rodrigues I.M.S.M.M., Spindola B.F. & Botteon P.T.L. [Biochemical and oxidative profile of horse used for a simulatedbarrel racing.] Perfil bioquímico e oxidativo de cavalos usados em prova simulada de três tambores. Revista Brasileira de Medicina Veterinária, 38(Supl.2):93-100, 2016. Programa de Pós-Graduação em Medicina Veterinária (Patologia e Ciências Clínicas), Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR-465 Km 7, Seropédica, RJ 23851-790, Brasil. E-mail: paulobotteon@gmail.com The barrel racing is characterized as an exercise with predominantly anaerobic metabolism. Aiming to evaluate the activity of serum enzymes creatine kinase (CK), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH), the enzymatic antioxidant defense through the enzymes glutathione peroxidase (GPx), superoxide dismutase (SOD) and oxidative damage means the concentration of malondialdehyde (MDA), six horses were used in a barrel racing simulated. Significant differences were observed between the times of collection in the serum activity of the enzyme AST, increasing in 4h after the race, but with normal values in the next 24 hours. The CK activity also showed significant difference compared with the rest, and higher values immediately after exercise and at 4 h after the test. The LDH activity values were higher in 4h after the race but with a significant difference compared to rest. The SOD activity showed no significant difference, as the GPx activity showed higher values in the 24 hours after the race. The MDA values increased significantly immediately after the evidence was showing that lipid peroxidation. Anaerobic exercise promoted an increase of the indicator enzymes of muscle damage and in oxidative stress biomarker.